(untitled) (Research, Society and Development, 2022)
The main objective of this work was to analyze the pattern of prescription of psychiatric drugs before and during the pandemic by the new coronavirus in the Family Health Units in the municipality of Pinhais-PR. This is a retrospective pharmacoepidemiological study based on the collection of secondary data on the prescription of psychiatric drugs from the 11 Family Health Units in the municipality of Pinhais, Paraná, from 2018 to 2020. Computer systems were used to access information referring to: prescription, sex, active ingredient, Family Health Unit and year. In this study, gender inequalities in the pattern of prescription of psychiatric drugs are evident, even with a 10% increase in prescriptions for men during the pandemic, women continue to be asymmetrically psychiatrized and medicalized. It is considered that identifying the pattern of prescription and consumption of psychiatric drugs in Primary Health Care can contribute to drawing a line of care in the context of mental health during and after the Covid-19 pandemic, since a large part of users with mental disorders and psychological distress should be monitored at this level of care.